MEMBANGUN WAWASAN SEJARAH LOKAL SISWA DENGAN PENGUATAN SCAFFOLDING DALAM PEMBELAJARAN SEJARAH - Piki Setri Pernantah (Diakronika, 2017)
History provides a valuable lesson. There are many diffecences, contradictions, and complex events that lead us to the gates of freedom. Therefore, teaching history in schools could be something very important. The current and furure challenge is on how we were able to fix all the problems occurred all this time in history lesson. The teacher should also be able to make history lesson to be more interesting, such as internalizing local history into the history lesson at schools so that the students are able to get close to reality and are not forgeting their local history. Building the students’ insight about local history with scaffolding reinforcement so that the students can develop their local historical insight optimally. Local history can serve as a source of ancestral history that should be preserved. In other words, local history can be a well that is never dry in drought, the values of wisdom for the realization of the ideals of a nation that is balanced, both physically and mentally. It adds to the material wealth of history and foster interest and knowledge of students in learning history. Therefore, this paper is intended to explain how the strategy to build students’ insight of local history with scaffolding reinforcement in teaching history at schools.